2011
DOI: 10.1182/blood-2010-04-281337
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA hypermethylation signature in acute myeloid leukemia directed by EVI1

Abstract: DNA methylation patterns are frequently dysregulated in cancer, although little is known of the mechanisms through which specific gene sets become aberrantly methylated. The ecotropic viral integration site 1 (EVI1) locus encodes a DNA binding zinc-finger transcription factor that is aberrantly expressed in a subset of acute myeloid leukemia (AML) patients with poor outcome. We find that the promoter DNA methylation signature of EVI1 AML blast cells differs from those of normal CD34 ؉ bone marrow cells and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 34 publications
4
75
0
Order By: Relevance
“…Promoter methylation was compared between patients with high or low MLL5 expression using normal CD34 + bone marrow cells (CD34 + NBM) as baseline ( Figure 5A and B). 31 In total, 341 and 71 probe sets were differentially methylated in CBF-and CN-AML patients with high MLL5 expression, respectively, with absolute difference in methylation more than 2 and adjusted P less than 0.01 ( Figure 5C). Among them, 91% (312 of 341) and 83% (59 of 71) were significantly hypermethylated in MLL5 high-expressing CBF-and CN-AML patients, respectively, whereas only 9% (29 of 341) and 17% (12 of 71) were hypomethylated.…”
Section: High Mll5 Expression Is Associated With Increased Dna Methylmentioning
confidence: 98%
“…Promoter methylation was compared between patients with high or low MLL5 expression using normal CD34 + bone marrow cells (CD34 + NBM) as baseline ( Figure 5A and B). 31 In total, 341 and 71 probe sets were differentially methylated in CBF-and CN-AML patients with high MLL5 expression, respectively, with absolute difference in methylation more than 2 and adjusted P less than 0.01 ( Figure 5C). Among them, 91% (312 of 341) and 83% (59 of 71) were significantly hypermethylated in MLL5 high-expressing CBF-and CN-AML patients, respectively, whereas only 9% (29 of 341) and 17% (12 of 71) were hypomethylated.…”
Section: High Mll5 Expression Is Associated With Increased Dna Methylmentioning
confidence: 98%
“…Epigenetic modification of the CEBPA promoter regions was also described and CEBPA hypermethylation appeared to be favorable prognostic marker in addition to NPM1 mutation with lack of FLT3-ITD and CEBPA bi-allelic, double mutations (Hackanson et al, 2008;Szankasi et al, 2011). Lugthart et al (2011) found that the promoter DNA methylation signature of EVI1 AML blast cells differed from normal bone marrow cells and other AMLs and contained many hypermethylated genes. EVI1 was observed to physically interact with DNA methyltransferases 3A and 3B and colocalize with them in nuclei and complex is involved in EVI1-mediated transcriptional repression.…”
Section: Dna Methylation Arraysmentioning
confidence: 99%
“…EVI1 was observed to physically interact with DNA methyltransferases 3A and 3B and colocalize with them in nuclei and complex is involved in EVI1-mediated transcriptional repression. Cases with the significantly higher levels of EVI1 are associated with many more methylated genes (Lugthart et al, 2011).…”
Section: Dna Methylation Arraysmentioning
confidence: 99%
“…A recent study using DNA microarray platforms in 344 patients described 16 epigenetically distinct groups, nine of which were associated with specific molecular subgroups of AML (CEBPA, NPM1, AML-ETO1, CBFb-MYH11 and PML-RARA) [57]. A number of recent reports have also identified aberrant methylation profiling in AML associated with several molecular mutations including EVI1 [58], MLL [59] and CEBPA [60]. There are also novel approaches such as the use of deep sequencing platforms that can provide a more comprehensive coverage of methylation profiling in cancer samples.…”
Section: Epigenetic Modifications: Dna Methylationmentioning
confidence: 99%